Organic cultivation of yellow passion fruit using tall seedlings with long root systems - Silva, Nilciléia Mendes; Araújo Neto, Sebastião Elviro; Souza, Luís Gustavo de Souza; Uchôa, Thays Lemos; Ferreira, Regina Lúcia Félix (Comunicata Scientiae, 2019)
Studies related to adaptation to the environment and different conditions of water availability contribute to decision-making regarding the management of any crop to be implanted. Accordingly, this work aimed to evaluate the yield and quality of organic yellow passion fruit cultivated in a long root system in dryland conditions. The experimental design was in randomized blocks, with five treatments and four replications with four plants each. The treatments consisted of the alteration of the length of the root system, namely: T1 = 25 cm; T2 = 50 cm; T3 = 75 cm; T4 = 100 cm; and T5 = 125 cm. At 120 days after emergence (DAE), the seedlings were transplanted to the field and the following variables were evaluated: plant height (cm) and base diameter (mm) at 120 DAE; total titratable acidity (TTA), total soluble solids (TSS), Ratio (TSS/TTA); and fruit yield. The cultivation of tall seedlings with a long root system provides the maintenance of production during the dry season. The TTA, TSS, and the ratio do not change when modifying the length of the root system, although they do change with the harvest season. The cultivation of passion fruit in an organic system using plants with a long root system with an estimated length of 114 cm provides a higher fruit yield (7,472 kg ha-1) in 22 months of cultivation.